Routledge handbook of elite performance sport (The Routledge International Handbook Series, 2019)
The Routledge Handbook of Elite Sport Performance is the first book to examine a broad span of performance and support issues in contemporary elite sport; including coaching, sports science and medicine, leadership and management, operating in different societies, living in the system as a performer, and future developments in the domain.